EFFECT OF DIFFERENT NUTRITIONAL STRATEGIES ON THE GROWTH OF BROILER CHICKENS IN AN INTENSIVE PRODUCTION SYSTEM (REMUNOM, 2025)
The present study investigated the effects of two distinct nutritional strategies on the zootechnical performance of Pesadão Vermelho (Red Bro) broilers reared under an intensive production system. The experiment was conducted at ETEC Sebastiana Augusta de Moraes, using 20 one-day-old chicks distributed into two treatments (n = 10): Treatment 1 (T1), fed a diet formulated by the institution without additives, and Treatment 2 (T2), fed a commercial balanced feed provided in three nutritional phases. The experimental period lasted 90 days, during which weight gain (WG), feed intake (FI), and apparent feed conversion (AFC) were evaluated. The results revealed substantial differences between treatments: T2 showed superior performance, with an average weight gain of 3,050 g, a feed conversion ratio of 7.21, and a survival rate of 90%. In contrast, T1 exhibited poor performance, with an average weight gain of 270 g, an AFC of 12.96, and a survival rate of only 40%. The high mortality observed in T1, including six deaths attributed to hypothermia, was associated with the nutritional inadequacy of the formulated diet, which compromised growth, feed efficiency, and thermoregulatory capacity. It is concluded that appropriate nutritional formulation and proper thermal management are critical to productivity and animal welfare in intensive broiler production systems. The use of commercially balanced diets proved essential to optimizing zootechnical performance and ensuring greater economic viability.